Adhesion of Leukocytes to Cerebral Venules Precedes Neuronal Cell Death and Is Sufficient to Trigger Tissue Damage After Cerebral Ischemia - Sienel, Rebecca Isabella; Kataoka, Hiroharu; Kim, Seong-Woong; Seker, Fatma Burcu; Plesnila, Nikolaus (Frontiers in Neurology, 2022)
Background Leukocytes contribute to tissue damage after cerebral ischemia; however, the mechanisms underlying this process are still unclear. This study investigates the temporal and spatial relationship between vascular leukocyte recruitment and tissue damage and aims to uncover which step of the leukocyte recruitment cascade is involved in ischemic brain injury. Methods Male wild-type, ICAM-1-deficient, anti-CD18 antibody treated, or selectin-deficient [fucusyltransferase (FucT IV/VII−/−)] mice were subjected to 60 min of middle cerebral artery occlusion (MCAo). The interaction between leukocytes and the cerebrovascular endothelium was quantified by in vivo fluorescence microscopy up to 15 h thereafter. Temporal dynamics of neuronal cell death and leukocyte migration were assessed at the same time points and in the same tissue volume by histology. Results In wild-type mice, leukocytes started to firmly adhere to the wall of pial postcapillary venules two hours after reperfusion. Three hours later, neuronal loss started and 13 h later, leukocytes transmigrated into brain tissue. Loss of selectin function did not influence this process. Application of an anti-CD18 antibody or genetic deletion of ICAM-1, however, significantly reduced tight adhesion of leukocytes to the cerebrovascular endothelium (-60%; p < 0.01) and increased the number of viable neurons in the ischemic penumbra by 5-fold (p < 0.01); the number of intraparenchymal leukocytes was not affected. Conclusions Our findings suggest that ischemia triggers only a transient adhesion of leukocytes to the venous endothelium and that inhibition of this process is sufficient to partly prevent ischemic tissue damage.